Mistreated Becker’s nevus. - Milano, A. (European Journal of Pediatric Dermatology, 2016)
Becker’s nevus begins early in life, sometimes at birth, with a hypermelanic spot to become more evident or sometimes be noticed for the first time in the peripubertal period due to the appearance of terminal hairs on the dark stain. This finding, coupled with increased frequency in the male and the localization on the nevus of pityriasis versicolor lesions and acne (1), suggest that the nevus is sensitive to androgens. The diagnosis of Becker’s nevus is easy when the hyperpigmentation is associated with hypertrichosis. Some difficulties even in the presence of hypertrophic hairs, can arise with nevus leiomyoma (2) where, however, the hypertrophiec hairs are present from the earliest periods of life; more difficult is the differential diagnosis from hypermelanic nevus before puberty when the hypertrichosis in Becker’s nevus is not yet clear. In the actual case, the diagnostic mistake was probably related to non-interference of the dermatologist in the diagnostic process.